DAMPAK PERUBAHAN LANDSKAP TERHADAP KEANEKARAGAMAN IKAN DI SUNGAI KUMU KABUPATEN ROKAN HULU RIAU - Purnama, Arief Anthonius; Yolanda, Rofiza (Universitas Pasir Pengaraian, 2015)
Study about Impact of Lanskape Change to Fish Diversity at Kumu River wasconducted from March-October 2013. The objective of the sudy was to evaluated todiverstity and morphology variation of fish at kumu river by using fishnet on samplinglocation (pit land, settlements and palm oil plantation). Total 558 ind, 7 family and 29species were obtained, they are Bagridae (2 species), Chandidae (1 species),Cobitidae (2 spesies), Cyprinidae (20 species), Hemiramphidae (1 species),Pristolepididae (1 species), Siluridae (2 spesies). Diversity index (H) was ranged from1.74 -1.95. Morfologycal variation from the species were not significant on p>0.05.